Chefferie, Bétail et Politique : Un notable kanak contre la revendication d'indépendance en Nouvelle-Calédonie - Trépied, Benoît (Anthropologica, 2013)
This paper provides an ethnography of indigenous activism against independence in New Caledonia, through the case of Auguste Poadja, a Kanak "loyalist" leader from the rural municipal district of Koné. Beyond classical explanations in terms of "alienation," his political commitment was related in practical terms to a strategy of local domination, based on collaboration with both the French State and the white settlers. In this perspective, his hostility to decolonization reflected his refusal to have the rules of the "colonial game"—which he had been playing both as a "grand chef" and a "stockman"— changed. While analysing local stakes and conflicts articulated to the wider debate on independence, this historical ethno graphy of Kanak political "loyalism" eventually underlines the complexity of colonial dynamics when seen "from below."